Skeletal and Cardiac Muscle Disorders Caused by Mutations in Genes Encoding Intermediate Filament Proteins - Maggi, Lorenzo (Int J Mol Sci, 2021)
Intermediate filaments are major components of the cytoskeleton. Desmin and synemin, cytoplasmic intermediate filament proteins and A-type lamins, nuclear intermediate filament proteins, play key roles in skeletal and cardiac muscle. Desmin, encoded by the DES gene (OMIM *125660) and A-type lamins by the LMNA gene (OMIM *150330), have been involved in striated muscle disorders. Diseases include desmin-related myopathy and cardiomyopathy (desminopathy), which can be manifested with dilated, restrictive, hypertrophic, arrhythmogenic, or even left ventricular non-compaction cardiomyopathy, Emery–Dreifuss Muscular Dystrophy (EDMD2 and EDMD3, due to LMNA mutations), LMNA-related congenital Muscular Dystrophy (L-CMD) and LMNA-linked dilated cardiomyopathy with conduction system defects (CMD1A). Recently, mutations in synemin (SYNM gene, OMIM *606087) have been linked to cardiomyopathy. This review will summarize clinical and molecular aspects of desmin-, lamin- and synemin-related striated muscle disorders with focus on LMNA and DES-associated clinical entities and will suggest pathogenetic hypotheses based on the interplay of desmin and lamin A/C. In healthy muscle, such interplay is responsible for the involvement of this network in mechanosignaling, nuclear positioning and mitochondrial homeostasis, while in disease it is disturbed, leading to myocyte death and activation of inflammation and the associated secretome alterations.